The Coverage of Situation of Western Armenians and Cilician Armenian’s Massacre in 1909 in the Pages of Egyptian Armenian Periodical “Arshalouys” - Myasnik Esoyan (Banber Arevelagitut'yan Instituti, 2025)
The administrative, economic, educational and military reforms carried out by the Wali of Egypt Muhammad Ali made Egypt a strong and stable state, laying a solid foundation for its development. The reforms of Muhammad Ali also had a positive impact on the Egyptian Armenian community. By the end of the 19th century, Armenian cultural life in Egypt had become more active, the number of schools had increased, new cultural and educational unions and organizations had appeared, and new periodicals were being published. At the beginning of the 20th century, Armenians occupied a prominent place in the Egyptian society. Armenians had churches, schools, cafes, and various Armenian newspapers were published in Egypt. Additionally, Armenians were the most prominent distributors of tobacco - there were many Armenian kiosks in various markets around the country. Around town, one could often meet an Armenian shoemaker, pharmacist, baker, doctor, teacher, tailor, etc.